The prevalence of lacunar infarct decreases with aging in the elderly: a case-controlled analysis - Cai Z (Dove Medical Press, 2016)
Zhiyou Cai,1 Wenbo He,1 Chuan-yong Peng,2 Jin Zhou,2 Qi-lan Xu,2 Zong-shan Wu2 1Department of Neurology, Renmin Hospital, Hubei University of Medicine, Shiyan Renmin Hospital, Shiyan, Hubei Province, 2The Examination Center of Magnetic Resonance Imaging, the Lu’an Affiliated Hospital of Anhui Medical University, Lu’an People’s Hospital, Lu’an, Anhui Province, People’s Republic of China Background and purpose: Lacunar infarct (LI) is well known as a heterogeneous primary disorder of cerebral small vessel. Compelling results have demonstrated that age is a risk factor to the prevalence of LI. However, the relationship between age and the prevalence of LI remains obscure. It is essential to note the relationship between age and the prevalence of LI through more clinical data. Methods: A total of 3,500 patients were included in the case-controlled study. All data were collected from the Examination Center of Magnetic Resonance Imaging, Lu’an People’s Hospital from January 2014 to December 2015. A primary discharge diagnosis of LI was done, and all subjects were evaluated as retrospective data. The relationship between the risk factors and the prevalence of diabetes and the relationship between age and the prevalence of diabetes was analyzed. A chi-square test was used to analyze the associations between different variables. A one-way analysis of variance was used to test the equality of three or more means at one time by using variances. Statistical significance was defined as a P-value of <0.05. Results: The one-way analysis of variance demonstrated that the prevalence of LI increased with age before 60 years and decreased with age after 69 years. The same results were found in both the male and the female subjects. These results showed that the age-related risk factors (hypertension, diabetes, cerebral infarct, cardiovascular diseases, smoking, and drinking) have no relationship with the prevalence of LI on the basis of age. There is a significant difference among the different age ranges (P=0.0006). Two-tailed P-value (unpaired t-test) showed the mean significant difference between 30–39 years and 40–49 years (P=0.009) and between 70–79 years and 80–100 years (P=0.0196). F-test (to compare variances) demonstrated that the variances of the different age ranges are significantly different between 30–39 years and 40–49 years (P=0.0002), between 40–49 years and 50–59 years (P=0.0424), and between 70–79 years and 80–100 years (P=0.0003). Conclusion: The age-related risk factors (hypertension, diabetes, cerebral infarct, cardiovascular diseases, smoking, and drinking) have no relationship with the prevalence of LI on the basis of age. A decreasing prevalence of LI with aging occurs in the elderly, while the prevalence of LI increases with aging in the young and in adults. This investigation implicates that age is not a risk factor for LI in the elderly. Keywords: lacunar infarct, prevalence, age, risk factor